A Review on the Impact of Silver Nanoparticles on Soil Microorganisms and Bioremediation as Heavy Metal Removal Technology - Hartati Oktarina; Teuku Mukhriza (Jurnal Serambi Engineering, 2021)
The increasing and varied use of silver nanoparticles (AgNPs) as antimicrobial on consumer products increases the risk of the nanomaterial release into the environment and potentially harm beneficial microorganisms in soil. Any change in soil microbial composition will lead to soil quality degradation that eventually reduce crop productivity. The negative effect of AgNPs on soil microorganism has been reported by researchers. There are technologies employed to remove heavy metals from soil such as chemical, physical, and biological technique. However, chemical and physical techniques have some disadvantages e.g high cost and partial removal. Therefore, biological technique including the use of microorganisms (bioremediation) become more favourable. The technique is considered as cost effectiveness and environmentally sustainable method. The present paper summarizes the impact of AgNPs on soil microorganisms and the use of microorganisms (bacteria, fungi, algae, and yeast) to eliminate heavy metals pollution in soil.